Aplicación de procesos biológicos como medida de remediación para recuperar suelos limo-arcillosos contaminados con gasolina - Toledo Moran, Bella Karina (2009)
This present work develops the topic "Recovery of soils contaminated with hydrocarbons." For such an effect is considered the bioremediation’s treatment in sand-slim-clay from the alluvial soil samples of the slim fan Mayor contaminated with gasoline from the fuel storage tanks of a petrol station with a surface area of 1396 m2. Hydrocarbon contamination was occurred due to leaks in the storage tank. The spill undertook a considerable amount of soil which was removed 4 m3. of contaminated material for remediation in cells treated ex-situ. Bioremediation treatment was performed in cells constructed especially for the remediation process, with techniques that help to the transformation’s process of pollutants by chemical reactions on the part of microorganisms through oxidation and reduction reactions, absorption, ion exchange and chelation reactions. Some of the bacterias used in the remediation process were Clostririum, although the presence of Actinomyces naturally appeared in the contaminated soil.